(untitled) (Contemporary Education and Teaching Research, 2020)
:In the course of digital signal processing, MATLAB software can be used in combination to change the traditional teaching form, to show students rich teaching content, to stimulate students’ interest in learning and to improve teaching quality.This paper first introduces the characteristics of digital signal processing course, and then analyzes the advantages of MATLAB software and digital signal processing course. The application of MATLAB software in digital signal processing course teaching is explored in detail in order to provide reference for teaching practice.